3,4-Diaminopyridine-evoked norepinephrine release and B-50 (GAP-43) phosphorylation - Huang Hua-Yu; Tang Tong; Chen Xiu-Fang (Acta Pharmacologica Sinica, 2016)
3,4-Diaminopyridine (3,4-DAP 100 mumol.L-1) evoked [3H]norepinephrine ([3H]NE) release in rat hippocampal slices preincubated with [3H]NE and superfused with medium with or without Ca2+. Phorbolester 4 beta-phorbol 12, 13, dibutyrate 1 mumol.L-1) enhanced and polymyxin B (100 mumol.L-1) inhibited the release of [3H]NE under both conditions. The neuron-specific protein B-50 is a major presynaptic substrate of protein kinase C and involved in exocytosis. Using in situ protein phosphorylation analyzed by SDS-PAGE and autoradiography, we observed that B-50 phosphorylation was significantly decreased by 3,4-DAP in the presence of extracellular Ca2+ and completely inhibited by removal of extracellular Ca2+. It was suggested that B-50 phosphorylation was not involved in 3,4-DAP-evoked [3H]NE release.